2017
DOI: 10.17957/tpmj/17.4169
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Complications in Open Surgery Versus Laparoscopic Surgical Management of Varicocele Among Adolescents at a Tertiary Care Hospital

Abstract: ABSTRACT… Objectives:To compare frequency of complications in open surgery versus laparoscopic surgical management of varicocele among adolescents at a tertiary care hospital. Study Design: Randomized controlled trial (RCT) study. Setting: Unit-I Department of General Surgery, Nishtar Medical College and Hospital, Multan. Period: January 2014 to February 2015. Material and methods: Group A was managed by open surgery while group B patients had undergone laparoscopic management. All data were analyzed by SPSS -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This is consistent with the other studies that showed that majority of primary varicoceles were present on the left side. Hasan et al 10 reported that 86.3% of varicoceles were on the left side, whereas Abbas et al 11 revealed that 82% of varicoceles were mainly left-sided. Other studies 1,12 suggested that 78-93% of primary varicoceles were left-sided.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the other studies that showed that majority of primary varicoceles were present on the left side. Hasan et al 10 reported that 86.3% of varicoceles were on the left side, whereas Abbas et al 11 revealed that 82% of varicoceles were mainly left-sided. Other studies 1,12 suggested that 78-93% of primary varicoceles were left-sided.…”
Section: Discussionmentioning
confidence: 99%